Potensi Jangka Panjang Pengembangan Program PLTSa Kota Surabaya dalam Perspektif Politik Lingkungan - Marwah Hermansyah, Andi; Muhammad, Muhammad; Yunus, Ariana (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
This paper aims to show the potential sustainability of the Waste Power Plant (PLTSa) policy implementation in Surabaya City. PLTSa is a central government program designed to increase waste processing into renewable energy. Surabaya City is one of 12 cities that have been targeted in the design of PLTSa. However, each targeted city has different urban characteristics so that Surabaya City needs a more in-depth study regarding the implementation of PLTSa and can be a parameter for other cities in implementing PLTSa programs in each region. Several aspects of the policy review study should be conducted by the city government to determine the extent to which Surabaya City can implement the program, including economic, and environmental aspects. Based on the literature review research conducted, Surabaya City can potentially implement the sustainability of PLTSa development if it fulfills the economic and environmental aspects of the study. The economic aspect looks at the extent to which the PLTSa budget can help with local revenue costs. And the environmental aspect looks at the extent to which the PLTSa program is able to minimize existing environmental damage.